Comparative Analysis of Cryptocurrency in Forms of Bitcoin, Stock, and Gold as Alternative Investment Portfolio in 2014' 2017 - Radinka Dynand Mahessara; Budi Rustandi Kartawinata (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This research is based on the phenomenon of new investment instrument called Cryptocurrency-Bitcoin which becomes popular in recent years. Based on that phenomenon, this research tries to search which is the best investment instrument from three instruments such as Bitcoin, stocks, and gold. The research method used is quantitative method with the type of research is comparative descriptive. In this study, the authors use Sharpe, Treynor and Jensen index approach to evaluate the performance. This study intends to do a comparison from the index using the data of the investment instrument in the period of January 2014 to August 2017. The study sample was taken from price result from every investment instrument during the period of study. The result shows that Bitcoin is the best instrument because based on Sharpe, Treynor, and Jensen value the return is better than the other two instruments.